2012
DOI: 10.1371/journal.pone.0051090
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Gene and Gene-Sex Epistatic Interactions of MiR146a, IRF5, IKZF1, ETS1 and IL21 in Systemic Lupus Erythematosus

Abstract: Several confirmed genetic susceptibility loci involved in the interferon signaling and Th17/B cell response for SLE in Chinese Han populations have been described. Available data also indicate that sex-specific genetic differences contribute to SLE susceptibility. The aim of this study was to test for gene–gene/gene-sex epistasis (interactions) in these known lupus susceptibility loci. Six single-nucleotide polymorphisms (SNPs) in MiR146a, IRF5, IKZF1, ETS1 and IL21 were genotyped by Sequenom MassArray system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Recent studies showed that the rs10488631 of IRF5 was significantly associated with SLE in an Egypt population [32]. And the allele distribution and gene-gene interactions of IRF5(rs4728142) MiR146a, IKZF1, ETS1 and IL21 have been identified in a Chinese Han population [33]. Thus, it is necessary to detect a larger number of SNPs of IRF5 with the correlation to SLE in a further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the rs10488631 of IRF5 was significantly associated with SLE in an Egypt population [32]. And the allele distribution and gene-gene interactions of IRF5(rs4728142) MiR146a, IKZF1, ETS1 and IL21 have been identified in a Chinese Han population [33]. Thus, it is necessary to detect a larger number of SNPs of IRF5 with the correlation to SLE in a further study.…”
Section: Discussionmentioning
confidence: 99%
“…although genome-wide association studies (GWas) reliably determine sle risk locations, some genetic predisposing factors may differ between populations. The complex genetic background of sle pathogenesis resides in variation of gene expression or in functional variants of members of multiple signalling pathways, immunologically active molecules or both 65 . some association studies focused on particular sNps of mirs genes and autoimmune diseases have already been performed, but failed to find any association with sle.…”
mentioning
confidence: 99%
“…47 ). on the other hand, leng et al performed a gene-gene interaction analysis of mir-146a (rs57095329) and il-21 (rs907715 and rs2221903), irF-5, iKZF-1 and ets-1 (rs6590330), using direct counting and a chi-square test with a 2×2 factorial design, and found no interaction of mir-146a, in particular with ets-1 65 . The ets-1 rs6590330 sNp is in high linkage disequilibrium with the rs1128334 sNp (r 2 = 0.97) (ref.…”
mentioning
confidence: 99%
“…Several polymorphisms in the IL-21 gene have been identified and several studies have been carried out to identify whether IL-21 polymorphisms were associated with SLE susceptibility (Sawalha et al, 2008;Hughes et al, 2011;Leng et al, 2012;Ding et al, 2012;Lan et al, 2014). Most of the studies focused on IL-21 rs907715 and rs2221903 polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although possible associations of the IL-21 polymorphisms with SLE were reported, and many case-control studies were further performed to identify the association between IL-21 rs907715 and rs2221903 polymorphisms and SLE (Sawalha et al, 2008;Hughes et al, 2011;Leng et al, 2012;Ding et al, 2012;Lan et al, 2014). However, results from these studies were inconsistent, which may be due to the limitations in sample size and differences in ethnic populations.…”
Section: Introductionmentioning
confidence: 99%